Strontium adsorption and desorption in wetlands: Role of organic matter functional groups and environmental implications. (15th April 2018) - Boyer, Antoine; Ning, Paris; Killey, Doug; Klukas, Martin; Rowan, David; Simpson, Andre J.; Passeport, Elodie
Abstract: Strontium (Sr) is a chemical element that is often used as a tracer in hydrogeochemical studies, and is ubiquitously distributed as a radioactive contaminant in nuclear sites in the form of strontium-90 (Sr-90). At the interface between groundwater and surface water, wetlands possess unique hydrogeochemical properties whose impact on Sr transport has not been investigated thoroughly. In this study, the adsorption and desorption of Sr was investigated on six natural wetland substrates and two mixes of exogenous media and wetland sediment: winter and summer wetland sediments, decayed cattails, wood, leaf litter, moss, bone charcoal, and clinoptilolite. The composition of the organic matter was characterized using carbon-13, solid phase Nuclear Magnetic Resonance analysis. The range of the substrates' adsorption coefficients obtained could be explained by factors indicative of proteins in the organic matter, which were shown to support strong and poorly reversible Sr adsorption. In contrast, the proportion of carbohydrates and lignin were found to be indicative of lower adsorption coefficients and higher desorption. The implications of these results for Sr pollution remediation in wetlands are discussed. Graphical abstract: Image 1 Highlights: Strontium adsorption and desorption on wetland substrates were studied. Wetland sediments showed strong and poorly reversible strontium adsorption. Proteins in the organic substrates played a key role in the retention of strontium. When mixed with sediment, both engineered media showed more reversible adsorption. Wetlands have potential to mitigate strontium pollution.